Experimental Study on Performance of Crushed-Rock Embankment with Heat-Induced Asphalt Pavement - Chen, Donggen; Wang, Shuangjie; Zhang, Xiong; Chen, Jianbing; Jin, Long (Transportation Geotechnics, 2019)
Previous numerical and field studies have confirmed effectiveness of the crushed-rock embankment (CRE) in protecting permafrost foundations in cold regions. However, some recent field monitoring data indicated that the CRE was not effective enough to prevent the permafrost foundations from thawing in some highway applications. The undermined effectiveness of the CRE was attributed to the strong heat absorption associated with the black asphalt pavement which absorbed more heat compared with lighter-colored surfaces. In order to strengthen the cooling effect of CRE in highway application, the composite CRE section with the heat-induced asphalt pavement (the composite CRE section) was presented. And then, the indoor laboratory model tests were performed to investigate the cooling performances of two sections: one is the composite CRE section, the other is the control CRE section with the conventional asphalt pavement (the control CRE section). Various sensors were installed at different locations of the two test sections to monitor the temperature, wind speed, and heat flux in order to better understand the working mechanisms of the different CRE structures. The test results showed that: (1) the heat-induced asphalt pavement increased the heat release in cold cycles, which was conducive to generate natural convection of the CRE. The cooling effect of the composite CRE section on the foundation was better than that of the control CRE section. (2) The maximum velocity of natural convection of crushed-rock layer in the composite CRE section was bigger than that of the control CRE section. The duration of the convection stage in the composite CRE section was longer than that of the control CRE section. (3) In warming cycles, the heat flux in the composite CRE section was slightly larger than that in the control CRE section. In cooling cycles, the heat flux in the composite CRE section was much smaller than that in the control CRE section. By comparing the cooling effects, air convective characteristics, and transient ...